High resolution modeling of western Alaskan tides and storm surge under varying sea ice conditions. (September 2019) - Joyce, Brian R.; Pringle, William J.; Wirasaet, Damrongsak; Westerink, Joannes J.; Van der Westhuysen, Andre J.; Grumbine, Robert; Feyen, Jesse
Abstract: A depth-integrated high resolution (down to 25–50 m) tide and storm surge model has been developed for the Alaska region with a focus on the coasts of western Alaska. The model uses the ADCIRC basin-to-channel scale unstructured grid circulation code forced with Climate Forecast System version 2 reanalysis meteorology. The tidal solution has been validated at 121 shelf and nearshore stations, with lower overall errors than a data assimilated tidal model (FES2012). The ADCIRC model shows considerable skill at simulating tide and coastal surge, and resulting overland flooding on the Yukon–Kuskokwim Delta, during both summer and winter storms. The root-mean-square-error of the model does not exceed 20 cm at any station, outperforming the Global Ocean Forecasting System (GOFS 3.1), a 1/12 ∘ data assimilated ocean general circulation model which is coupled to sea ice physics. The ADCIRC model incorporates the effect of sea ice through parameterizations of the wind drag coefficient, modifying the air–sea momentum transfer under ice coverage. Three large winter storms with distinctly different ice coverages along the coasts of western Alaska were chosen to exhibit the variable effect of sea ice on the resulting storm surge. Under forming coastal ice coverage, local increases in water levels due to ice is seen in coastal areas, and under predominantly dense pack ice, an increase in momentum transfer in the marginal sea ice at the shelf break leads to an increase in sea levels across the entire Bering Sea, both commensurate with observations. Under the most variable ice fields, results are mixed, in part due to uncertainties in the air–sea–ice drag parameterization such as related to the assumption that sea ice drift and wind velocities are always well correlated. Including a description of sea ice drift and current speeds explicitly in the air–sea–ice drag formulation and considering wave–surge–ice interaction should improve the description of momentum transferred to the water column and resulting simulation of surge. Highlights: Overall, coastal tidal gauge errors are smaller than those from a data assimilated tidal model. Peak coastal surge is larger and closer to observations than simulated by operational ocean model. Severe overland flooding on the Yukon–Kuskokwim Delta is well captured during November 2011 storm. Including the effect of sea ice on air–sea drag increases peak surge towards observations. Including the effect of sea ice on air–sea drag increases month-long errors due to uncertainties.